Weimar and the Vatican, 1919-1933 : German-Vatican Diplomatic Relations in the Interwar Years - Stehlin, Stewart A., 1936- (Book collections on Project MUSE., 1983)
Demonstrating the important role of the Vatican in international affairs during this period, Stewart A. Stehlin provides the first full discussion of Weimar-Vatican relations from 1919 to 1933. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.